(untitled) (Global Journal of Management and Business Research, 2020)
A major assumption in much of the bank profitability literature is that banks are profit maximizers. It is in fact, one of the assumptions that are shared by all models reviewed in the area of bank profitability studies. To be sure, standard theory tells us that banks’ shareholders are aspiring maximum return (profits) for their investments and it is thereby managers as agents of shareholders’ pursue to maximize profits. Hence, banks’ primary objective is to maximize shareholders return on investment by maximizing revenues and minimizing costs. The focus of the current study is emphasized the importance of achieving a healthy Net Interest Margin (NIM), which is the main lifeline or core in the banking business. Hence, this is an empirical study based on a time series analysis of actual data published during the latest 12 years on key variables relating to NIM and Profit after Tax (PAT). The authors have attempted to describe the relationship among important variables covering the subject and finally, the latest trends between NIM and PAT. Accordingly, the objective of this study was based on verifying the general opinion on whether the NIM of the Sri Lankan Banking industry is on an undesired direction.